Improving the efficiency of management of domestic fitness clubs in modern conditions of functioning - Yuliia Leonova; Anastasiia Bondar; Svitlana Stadnyk (Слобожанський науково-спортивний вісник, 2020)
Purpose: to develop practical recommendations to improve the efficiency of management of domestic fitness clubs in modern conditions of functioning. Material and methods: to solve this goal, a set of scientific research methods was used: analysis of literary sources; analysis of documents; system analysis; organizational analysis; expert method, methods of mathematical statistics. The study was conducted on the basis of 10 fitness clubs in Kharkov. The group of experts included 50 clients of fitness clubs: 25 women and 25 middle-aged. Results: using the expert method, we determined the importance of the criteria for choosing a fitness club for clients. In the course of our research, it was found that the "most important" for the clients when choosing a fitness club is the cost of the subscription and the location of the fitness club, "medium" are the quality of equipment and the range of services; and the “least important” is the professionalism of the trainers and the quality of service. Conclusions: based on the results of the study, the authors have developed practical recommendations for the management and managers of fitness clubs, the implementation of which will ensure an increase in competitiveness and strengthening of positions in the fitness services market, as well as an increase in profits. Practical recommendations are aimed at enhancing marketing activities, expanding the advertising campaign and improving the pricing policy of fitness clubs, as well as improving management efficiency in order to introduce modern scientific developments and high-quality customer service, etc.